THU0140 Tofacitinib (CP-690, 550), an oral janus kinase inhibitor: Analysis of gastrointestinal adverse events across the rheumatoid arthritis clinical programme. (23rd January 2014) - Lee, E.B.; Curtis, J.R.; Riese, R.; Connell, C.; Chew, R.; Boy, M.; Maller, E.; Su, C.; Wang, L.; Bradley, J.
Abstract : Background: Tofacitinib (CP-690, 550) is a novel, oral Janus kinase inhibitor being investigated as a targeted immunomodulator in rheumatoid arthritis (RA). Objectives: To describe and report the incidence of gastrointestinal (GI) adverse events (AEs) that occurred in the tofacitinib RA programme up to 29 March 2011. Methods: Data from 5 randomised Phase 3 (P3) studies or 2 open-label long-term extension (LTE) studies were pooled. Patients (pts) were treated with tofacitinib 5 mg twice daily (BID), tofacitinib 10 mg BID, placebo (PBO; P3 only), or adalimumab (ADA; P3 only). Analyses of integrated safety data were from 3315 (P3; 2480 pt-y) and 3227 pts (LTE; 3118 pt-y) (LTE pts rolled over from P2 and P3). GI perforation data were analysed from P2 (1608 pts), P3, and LTE studies. Results: In P3 studies, exposure-adjusted event rates (EAER) (per 100 pt-y) of AEs (regardless of causality) coding to the GI System Organ Class and MedDRA preferred term, Month (Mo) 0-12, was numerically lower in pts receiving tofacitinib 5 mg BID (33.48), 10 mg BID (31.03) and ADA (21.23) vs PBO (49.87). In LTE, EAERs of GI AEs were 17.52 and 25.26 in the 5 and 10 mg BID groups, respectively. GI AEs included gastritis, constipation, diarrhoea, abdominal pain, dyspepsia, nausea and vomiting; diarrhoea (3.4%) and nausea (2.3%) were the most frequently reported with tofacitinib. EAERs for discontinuations (DCs) due to GI AEs in P3 (Mo 0-3, PBO-controlled period) were similar for tofacitinib (doses combined) (1.52) and PBO (1.93); EAER for ADA was 4.26. EAERs for DCs due to GI AEs for Mo 3-6 and > Mo 6 were similar to Mo 0-3. EAERs for DCs due to GI AEs in LTE were numerically lower vs P3: 0.72 (5 mg) and 0.34 (10 mg). Abdominal pain was the most common GI cause leading to DC (0.1%) with tofacitinib. Serious adverse events (SAEs) (all causality) due to GI disorders were uncommon in P3 and LTE. In P3, no GI SAE occurred in more than one pt in any dose group during Mo 0-3, 3-6 and >6. In LTE the most common abdominal SAEs were pancreatitis (4 pts, 0.12%) and cholecystitis (5 pts, 0.15%). To assess the occurrence of GI perforations, potential cases were retrospectively reviewed by Pfizer gastroenterologists based on pre-specified criteria. Ten cases of probable or definite perforation occurred in tofacitinib-treated pts; one resulted in death associated with appendicitis and sepsis. The overall GI perforation incidence rate was 0.18 (95% CI 0.095, 0.329) events per 100 pt-y. GI perforations primarily involved the lower GI tract (9 pts), and generally occurred in pts with other underlying risk factors, eg non-steroidal anti-inflammatory drugs (7 pts), glucocorticoid use (8 pts), or comorbidity of diverticulitis (3 pts). Conclusions: GI AEs occurred commonly in all treatment groups including PBO, but were uncommon causes for DCs. Serious GI AEs were uncommon. The rate of GI perforation falls between the rates reported for pts treated with tocilizumab (0.19) and TNF inhibitors (0.13). 1 References: Gout T et al. Clin Rheumatol 2011; 30: 1471-1474. Disclosure of Interest: E. B. Lee Consultant for: Pfizer Inc., J. Curtis Grant/Research support from: Pfizer Inc., Consultant for: Pfizer Inc., R. Riese Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., C. Connell Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., R. Chew Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., M. Boy Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., E. Maller Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., C. Su Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., L. Wang Shareholder of: Pfizer Inc., Employee of: Pfizer Inc., J. Bradley Shareholder of: Pfizer Inc., Employee of: Pfizer Inc.